Improvement capability and performance: a qualitative study of maternity services providers in the UK. (16th April 2018) - Darley, Sarah; Walshe, Kieran; Boaden, Ruth; Proudlove, Nathan; Goff, Mhorag
Abstract: Objective: We explore variations in service performance and quality improvement across healthcare organisations using the concept of improvement capability. We draw upon a theoretically informed framework comprising eight dimensions of improvement capability, firstly to describe and compare quality improvement within healthcare organisations and, secondly to investigate the interactions between organisational performance and improvement capability. Design: A multiple qualitative case study using semi-structured interviews guided by the improvement capability framework. Setting: Five National Health Service maternity services sites across the UK. We focused on maternity services due to high levels of variation in quality and the availability of performance metrics which enabled us to select organisations from across the performance spectrum. Participants: About 52 hospital staff members across the five case studies in positions relevant to the research questions, including midwives, obstetricians and clinical managers/leaders. Main Outcome Measure: A qualitative analysis of narratives of quality improvement and performance in the five case studies, using the improvement capability framework as an analytic device to compare and contrast cases. Results: The improvement capability framework has utility in analysing quality improvement within and across organisations. Qualitative differences in the configurations of improvement capability were identified across all providers but were particularly striking between higher and lower performing organisations. Conclusions: The improvement capability framework is a useful tool for healthcare organisations to assess, manage and develop their own improvement capabilities. We identified an interaction between performance and improvement capability; higher performing organisations appeared to have more developed improvement capabilities, though the meaning of this relationship requires further research.